Analysis of COVID-19 Preventive Behavior in Diabetes Mellitus Patients: A Literature Review - Hasyim, Hamzah; Putri, Gizka; Dale, Patricia (UI Scholars Hub, 2022)
The Coronavirus Disease 2019 (COVID-19) is a new human-infected coronavirus causing respiratory problems. The COVID-19 can affect people of all ages, but those with a record of chronic disease (comorbidity) are at higher risk of poor outcomes with the COVID-19. This study aimed to review COVID-19 preventative behavior in diabetes patients. Diabetes Mellitus (DM) is one of the comorbidities that aggravates COVID-19 in patients. Such patients are at risk of deteriorating critical conditions in the intensive care units (ICUs) and even death. Prevention is the best measure to avoid COVID-19, although it is currently considered adequate. This article reviewed 22 papers focusing on COVID-19, DM, COVID-19 in DM patients, COVID-19 preventive behavior, and COVID-19 knowledge, attitude, and practice in patients with chronic disease, while primary focusing on DM. It is revealed that diabetes patients at high risk of COVID-19 need to practice good preventive behaviors. Furthermore, it emphasizes that improving knowledge, encouraging positive attitudes, and implementing good COVID-19 preventive behaviors in DM patients requires education and access to the COVID-19 related health information.